Employability Competencies: Employer Expectations and Employer Satisfaction of Open University Malaysia's Graduates - Lim , Tina Swee Kim; Norziati, Mansor; Wardah Mohamad; Tuan Fatma Tuan Sulaiman; Hazalina Hashim; Nor Aisyah Fadil; Norlia Goolamally; Latifah Abdol Latif; Saedah Muda; Woo, Tai-Kwan; Santhi Raghavan (-, 2011)
Objectives of the Study The objectives of the study were to: (1) Find out the level of importance attributed by employers to the various employability competencies; (2) Find out the extent to which the employers are satisfied with OUM graduates' competencies; (3) Examine the extent to which the level of employer satisfaction differs from the level of importance attributed to the competencies; and (4) Examine the strengths and opportunities for improvement of OUM graduates with regard to employability competencies?